2012
DOI: 10.1590/s1519-70772012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes da defasagem na divulgação das demonstrações contábeis das companhias abertas brasileiras

Abstract: This work examines the determining factors affecting the timing of disclosures in quarterly and annual financial statements of Brazilian companies with shares that are listed on the Sao Paulo Stock Exchange with shares that composed the São Paulo Stock Exchange Index (IBOVESPA) during the period 1/1997 -2/2009. The determining factors were grouped into the following four dimensions: the complexity of operations, the characteristics of corporate governance, the level of information asymmetry, and the proprietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 35 publications
1
8
1
19
Order By: Relevance
“…Based on the literature on the timing of the delivery of financial information, we added control variables to the models used. Some of these variables have already been used in previous studies conducted on the lag in the delivery of information in the Brazilian market (Barcellos et al, 2014;Kirch et al, 2012;Paixão et al, 2017) and have been demonstrated to be related to the delivery date of financial statements.…”
Section: Research Design and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature on the timing of the delivery of financial information, we added control variables to the models used. Some of these variables have already been used in previous studies conducted on the lag in the delivery of information in the Brazilian market (Barcellos et al, 2014;Kirch et al, 2012;Paixão et al, 2017) and have been demonstrated to be related to the delivery date of financial statements.…”
Section: Research Design and Samplementioning
confidence: 99%
“…Bagnoli et al (2002) and Haw, Qi, and Wu, (2000) suggest that when the disclosure of information is delayed in relation to the date expected by the market, it is likely that the report released will contain bad news. This topic has not yet been explored in Brazil since the national literature has not considered timeliness in relation to the disclosure date expected by the market but rather in relation to the number of calendar days between the baseline date of the financial statements and the date of disclosure (Barcellos, Costa, & Laurence, 2014;Kirch, Lima, & Terra, 2012;Paixão, Avelino, & Takamatsu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…É importante ressaltar que, os gestores precisam definir a data de divulgação das demonstrações financeiras, observando se os benefícios desta divulgação mais rápida superam os custos gerados nesta ação (SENGUPTA, 2004;KIRCH;LIMA;TERRA, 2012). Assim, a escolha dos gestores em relação ao momento da divulgação não é totalmente discricionária, havendo um limite temporal tanto inferior (definido pela empresa, segundo seus interesses) quanto superior (definido pelo regulador) para que as demonstrações contábeis sejam tornadas públicas (BARCELLOS; COSTA JÚNIOR; LAURENCE, 2014).…”
Section: Prazo De Divulgação Dos Relatórios Financeirosunclassified
“…In such a context, the following studies have analyzed the determinants of SFS restatements and their consequences for the market: a) increase in restatements decreases the return of shares (Anderson & Yohn, 2002;Palmrose, Richardson, & Scholz, 2004); b) restatements have a negative relationship with the value of the company and with the market reaction (Hribar & Jenkins, 2004;Jategaonkar, Lovata, & Sierra, 2012;Palmrose et al, 2004;Mr. Silva;Wilson, 2008); c) fraudulent accounting reports are one of the main determinants for restatements (Albring, Huang, Pereira, & Xiaolu, 2013;Carpenter, 2007;DeFond & Jiambalvo, 1991;Palmrose et al, 2004); d) negative relationship between the auditors' fees and future restatements (Blankley, Hurtt, & MacGregor, 2012;Blankley, Hurtt, & MacGregor, 2014;Raghunandan, Read, & Whinesant, 2003;Stanley & DeZoort, 2007), or even positive (Kinney, Palmrose, & Scholz, 2004;Stanley & DeZoort 2007); e) lower probability of restatement by companies audited by the Big Four (Eshleman & Guo, 2014;Newton, Wang, & Wilkins, 2013), but results were also found audits conducted by the Big Four do not imply less restatement (Lobo & Zhao, 2013;Marques, Aires, Cerqueira, & Silva, 2016).…”
Section: Introductionmentioning
confidence: 99%